Eight-years trends and outcomes in TAVI performed in a high-volume center. (25th November 2020) - Tagliari, A; Haager, P.K; Miura, M; Russo, G; Pozzoli, A; Gavazzoni, M; Zuber, M; Joerg, L; Maisano, F; Taramasso, M
Abstract: Introduction: Since the first transcatheter aortic valve implantation (TAVI), remarkable changes in procedure features and patients' profile have been reported, making it a widespread treatment for severe aortic stenosis in all risk-class patients. Purpose: To evaluate TAVI contemporary trends and outcomes in the last 8 years in a high-volume TAVI center. Methods: Data of adult patients submitted to TAVI from April 2012 to April 2019 in a high-volume center were obtained from the Swiss TAVI registry, a prospective national multi-center database. Patients were divided according to implant period in two groups: 1) TAVI performed from 2012 to 2016, and 2) TAVI performed from 2017 to 2019. Results: Over a 8-years period, a total of 1485 procedures were performed, increasing from 95 in 2012 to 320 in 2018 (p<0.001). A remarkable modification in patients' profile and procedure characteristics can be seen in Table 1. Despite higher age and surgical risk, a significant decrease in 1-year mortality (6.8% vs. 3.2%; p<0.001) was observed in the last 3 years. This difference was especially notable in the subgroup of high-risk patients (STS score ≥8), who presented a decrease in 30-days (5% vs. 3.3%; p=0.001) and 1-year mortality (13.1% vs. 4.9%; p<0.001). In multivariate analysis, age (OR 1.05, 95% CI: 1.0–1.1), non-femoral access (OR 2.7, 95% CI: 1.2–6.0), and STS score (OR 1.07, 95% CI: 1.0–1.1) were independent predictors of in-hospital mortality, while male gender (OR 1.8, 95% CI: 1.0–3.2), chronic obstructive pulmonary disease (OR 2.1, 95% CI: 1.1–3.9), and STS score (OR 1.07, 95% CI: 1.01–1.14) were predictors of 1-year mortality. Conclusion: Significant changes in patients' profile and procedure characteristics were observed in the last 3 years of TAVI experience. Even performed in elderly and high-risk patients, TAVI was associated with low early and 1-year mortality. The Swiss TAVI registry offers a unique opportunity to monitor trends and outcomes in patient submitted to TAVI. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): APT is a Ph.D. study and her scientific research is supported by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (Capes) - Finance Code 001.